KEWAJIBAN AYAH TERHADAP ANAK AKIBAT TERJADINYA PERCERAIAN YANG HAK NAFKAH TIDAK DIMINTA DAN TIDAK DITETAPKAN DALAM PUTUSAN HAKIM (PUTUSAN NOMOR 496/PDT.G/2022/PA.KTP) - NIM. A1012191078, ALFIAN DARUSSALAM (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract In the divorce trial process between the Plaintiff and the Defendant, the Panel of Judges has made efforts to reconcile the two parties through mediation stages as regulated in the applicable laws and regulations. However, the mediation efforts did not produce results because each party remained adamant in their decision to divorce, the development of the trial, the Plaintiff changed his petitum and requested to be given custody of the two children. The Defendant did not object to the change in the request and stated his agreement to the custody request submitted by the Plaintiff. This change in petitum is an important part of the case examination process because it concerns the best interests of the child, which must be the main consideration in every decision related to child custody in divorce cases. Therefore, the formulation of the problem in this study is as follows: